2016
DOI: 10.1111/jpc.13408
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde continence enema in children with spina bifida: Not as effective as first thought

Abstract: We demonstrated a high rate of cessation with RCE in patients with spina bifida. This could not be explained by associated conditions, or by enema-related parameters. One possible explanation is the lack of ongoing outpatient support for the children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…King et al reported also important drop out of nearly half of patients (11/20) with PT in a group of spina bifida patients. Reason for drop out: balloon loss in 4/20, too difficult procedure in 4/20 and pain in 3/20 patients (12). Better patient selection (age, underlying disease, personality type, intellectual/…”
Section: Discussionmentioning
confidence: 99%
“…King et al reported also important drop out of nearly half of patients (11/20) with PT in a group of spina bifida patients. Reason for drop out: balloon loss in 4/20, too difficult procedure in 4/20 and pain in 3/20 patients (12). Better patient selection (age, underlying disease, personality type, intellectual/…”
Section: Discussionmentioning
confidence: 99%
“…In eight, enhanced quality of life was seen (significant results) (Ausili et al, 2010; Choi et al, 2015; Christensen et al, 2006,2008; Del Popolo et al, 2008; Kelly, Dorgalli, McLorie, & Khoury, 2017; Kim et al, 2013; Loftus et al, 2012). However, King et al (2017) reported no significant difference among users when compared with those no longer using TAI. Hamonet-Torny et al (2013) and Passananti et al (2016) presented no comparative (baseline) values but found that those still using TAI at follow-up experienced minor bowel dysfunction and found higher numbers of participants reporting mild or no problem, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…The most commonly reported adverse effect when using TAI was abdominal pain/discomfort, seen in eight studies (Ausili et al, 2010; Choi et al, 2015; Christensen et al, 2006; Faaborg et al, 2009; Kim et al, 2013; King et al, 2017; López Pereira et al, 2010; Patel et al, 2020). Other more common adverse effects were anorectal/perianal irritation/discomfort (Ausili et al, 2010; Christensen et al, 2006; Kim et al, 2013; Passananti et al, 2016; Patel et al, 2020), minor anal/rectal bleeding (Choi et al, 2015; Faaborg et al, 2009; Kim et al, 2013; Passananti et al, 2016), sweating (Ausili et al, 2010; Christiansen et al, 2006; Faaborg et al, 2009; López Pereira et al, 2010), fatigue (Faaborg et al, 2009; Kim et al, 2013), and/or general discomfort (Ausili et al, 2010; Christensen et al, 2006; Faaborg et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies report compliance to digestive tract treatments, but they are often weaker (less than 50%). 28 The two main causes of discontinuation of treatment were lack of efficacy (21.1%) and the occurrence of FI due to loose stools (13.5%). This highlights the importance of obtaining stools of normal to hard consistency.…”
Section: Discussionmentioning
confidence: 99%